2020
DOI: 10.1002/open.202000247
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Microwave‐Assisted Friedländer Quinoline Synthesis

Abstract: A microwave‐based methodology facilitates reaction of 2‐aminophenylketones with cyclic ketones to form a quinoline scaffold. Syntheses of amido‐ and amino‐linked 17β‐hydroxysteroid dehydrogenase type 3 inhibitors with a benzophenone‐linked motif were pursued using 2‐aminobenzophenone as building block. Two amido‐linked targets were achieved in modest yield, but when using microwave‐assisted reductive amination for the amino‐linked counterparts an unexpected product was observed. X‐ray crystallography revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Helen and coworkers optimized the Friedlander condition using 2‐aminophenyl ketone and other cyclic ketone in the acetic acid, acting as solvent and catalyst at 160°C temperature for 5 min under microwave conditions (Scheme 4), the results were obtained with good to excellent yields (Bailey et al, 2020).…”
Section: Quinoline Scaffoldmentioning
confidence: 99%
“…Helen and coworkers optimized the Friedlander condition using 2‐aminophenyl ketone and other cyclic ketone in the acetic acid, acting as solvent and catalyst at 160°C temperature for 5 min under microwave conditions (Scheme 4), the results were obtained with good to excellent yields (Bailey et al, 2020).…”
Section: Quinoline Scaffoldmentioning
confidence: 99%
“…Another Friedländer quinoline synthesis via rapid condensation of 2-aminophenylketones (116) with cyclic ketones (117, 1.5 equiv) to synthesize quinolines (118) under microwave irradiation in good yields at 160 °C has been accomplished by Potter et al (Scheme 39). [118] 3.5. Meatal catalysts…”
Section: Using Ketonesmentioning
confidence: 99%
“…Bailey et al in year 2020, reported microwave-assisted synthesis of Quinolines 260 following Friedlander pathway (Scheme 71). [111] This reaction was performed between 2-aminoaryl ketones 57 and cyclic/acyclic ketone molecules 259 while neat acetic acid played the role of solvent and catalyst at 160 °C under microwave condition for 5 minutes and the products were obtained in good yields.…”
Section: Scheme 67 Access To Dihydropyrimido-quinolinetrione Derivativesmentioning
confidence: 99%